Quaternary Carbonate and Evaporite Sedimentary Facies and Their Ancient Analogues 2010
DOI: 10.1002/9781444392326.ch15
|View full text |Cite
|
Sign up to set email alerts
|

The role of bacterial sulphate reduction in carbonate replacement of vanished evaporites: examples from the Holocene, Jurassic and Neoarchaean

Abstract: Vanished evaporites are well documented in the geological record, but many may go unrecognized because of a lack of obvious field or petrographic evidence, particularly in carbonates deposited in restricted settings where bacterial sulphate reduction (BSR) was active. An early stage in evaporite replacement by carbonates may be observed in modern salterns in Eilat, where gypsum crusts are colonized by stratified, endoevaporitic, microbial communities including sulphate-reducing bacteria (SRB). Here, BSR can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(103 reference statements)
1
0
0
2
Order By: Relevance
“…Thompson and Ferris () have shown that in high‐sulfate environments as pH approaches 7.9, gypsum becomes unstable and dissolution is favored. Dissolution of solid gypsum under similar conditions has been documented in other environments (Douglas, ; Wright & Kirkham, ; Wright & Oren, ), as well as in the Guerrero Negro gypsum crust mats (Vogel et al, , ). While high sulfate reduction rates often facilitate the deposition of CaCO 3 , only trace amounts of carbonate are observed in these crusts (Vogel et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…Thompson and Ferris () have shown that in high‐sulfate environments as pH approaches 7.9, gypsum becomes unstable and dissolution is favored. Dissolution of solid gypsum under similar conditions has been documented in other environments (Douglas, ; Wright & Kirkham, ; Wright & Oren, ), as well as in the Guerrero Negro gypsum crust mats (Vogel et al, , ). While high sulfate reduction rates often facilitate the deposition of CaCO 3 , only trace amounts of carbonate are observed in these crusts (Vogel et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…Актуалистическим доказательством замещения сульфата карбонатом является, к примеру, образование диагенетического карбоната по гипсу в гиперсолёных водоёмах Эйлата, Израиль, где гипсовые корки в диагенезе колонизируются стратифицированными, микробиальными сообществами, включая сульфатредуцирующие бактерии. В эфемерных высокомагнезиальных карбонатных осадках лагуны Куронг в Южной Австралии в периоды эвапоритизации гипс замещается пиритом, а карбонат представлен протодоломитом и гидромагнезитом (Wright, Kirkham, 2010).…”
Section: механизм диагенетического растворения сульфата при биосульфаunclassified
“…Это предполагает ведущую роль предлагаемого механизма удаления твёрдых сульфатов в результате снижения их концентрации в поровом растворе при биосульфатредукции. Для ряда докембрийских формаций, содержащих доломиты с признаками перекристаллизации, брекчирования и гнездовых текстур, напоминающих псевдоморфозы по гипсу, также предполагается былое присутствие эвапоритовых условий, несмотря на отсутствие самих характеристических минералов («исчезнувшие эвапориты (vanished evaporite)» (Wright, Kirkham, 2010)). В то же время некоторые разрезы раннего рифея КБА, к примеру, в сарапульской свите, содержали прослои красноцветных алевролитов с гнездами ангидрита (Мичурин и др., 2009) или эукариотические микрофоссилии (калтасинская свита ), что указывает на эвапоритовое карбонатное осадконакопление в оксидных условиях.…”
Section: заключениеunclassified